2021
DOI: 10.1016/j.jmgm.2021.107968
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor NF-κB as target for SARS-CoV-2 drug discovery efforts using inflammation-based QSAR screening model

Abstract: NF-κB is a central regulator of immunity and inflammation. It is suggested that the inflammatory response mediated by SARS-CoV-2 is predominated by NF-κB activation. Thus, NF-κB inhibition is considered a potential therapeutic strategy for COVID-19. The aim of this study was to identify potential anti-inflammation lead molecules that target NF-κB using a quantitative structure-activity relationship (QSAR) model of currently used and investigated anti-inflammatory drugs as the basis for screening. We applied an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Whereas, the augmented system is a double-edged sword for DILI in COVID-19 patients because it needs to convert parent drug into toxic reactive intermediates, e.g., ritonavir, to facilitate the detoxification of exogenous compounds. In addition, PXR played pleiotropic effects on DILI: this xenosensor could be inhibited by significant liver inflammatory response, attributing to CRS of COVID-19, via the crosstalk with NF-κB ( Zordoky and El-Kadi, 2009 ; Kanan et al, 2021 ). The p65 subunit, increased by IL-6 and other released cytokines, interacted with the PXR partner RXRα to inhibit hepatic metabolism system ( Moreau et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas, the augmented system is a double-edged sword for DILI in COVID-19 patients because it needs to convert parent drug into toxic reactive intermediates, e.g., ritonavir, to facilitate the detoxification of exogenous compounds. In addition, PXR played pleiotropic effects on DILI: this xenosensor could be inhibited by significant liver inflammatory response, attributing to CRS of COVID-19, via the crosstalk with NF-κB ( Zordoky and El-Kadi, 2009 ; Kanan et al, 2021 ). The p65 subunit, increased by IL-6 and other released cytokines, interacted with the PXR partner RXRα to inhibit hepatic metabolism system ( Moreau et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…ADMET and ADME (Absorption, Distribution, Metabolism, Excretion) properties of the 8 proposed molecules were calculated using pkCSM [68] and SwissADME [69] (ADME =Adsorption, Distribution, Metabolism, Excretion ) online tools. The carboxamides sulfonamide scaffold showed good pharmacokinetics with moderate absorption, satisfactory metabolic transformation and no toxicity as far as the inhibitory properties against SARS-CoV-2 is concerned.…”
Section: Study Of Admet Properties Using 3d-qsar and MDmentioning
confidence: 99%
“… 262 SARS‐CoV‐2 mediates inflammation by activating NF‐κB, so the development of drugs that inhibit NF‐κB is currently considered to be one of the potential treatment strategies for COVID‐19. 272 A clinical trial used the BTK inhibitor acalabrutinib to treat severe COVID‐19 patients, and the result showed that C‐reactive protein and IL‐6 levels were reduced, and patients' oxygen saturation improved. 273 Another study used diosmectite in the SARS‐CoV‐2 model, as diosmectite can bind to SARS‐CoV‐2 components and inhibit NF‐κB activation and CXCL10 secretion and inhibit downstream inflammation, indicating the potential value of diosmectite for COVID‐19‐related diarrhea.…”
Section: Nf‐κb and Inflammationmentioning
confidence: 99%